2019
DOI: 10.25165/j.ijabe.20191201.4360
|View full text |Cite
|
Sign up to set email alerts
|

Models for economic evaluation of multi-purpose apple harvest platform and software development

Abstract: An increasing number of U.S. apple growers are now interested in using harvest platforms to increase harvest productivity, expand labor pool, and alleviate tough working conditions. To maximize benefits, functions of thinning, pruning & training, and infield sorting have been or are to be incorporated into harvest platforms. Though growers are most concerned with economic benefits, few cost-benefit studies had been conducted on different platforms. In the meantime, economic analysis procedure is complex and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…conditions of farmers and agricultural workers that are generally linked to various musculoskeletal disorders [2][3][4]. Application of robotic solutions regarding crop monitoring and harvesting is considered to have significant beneficial effects on production profits [5], enabling faster and easier automated harvest and increasing crop quality and yield. Thus, the development of robotic technologies and their application in agriculture is becoming a growing topic of interest and consideration [6], with an increasing amount of research work being noticed in the last decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…conditions of farmers and agricultural workers that are generally linked to various musculoskeletal disorders [2][3][4]. Application of robotic solutions regarding crop monitoring and harvesting is considered to have significant beneficial effects on production profits [5], enabling faster and easier automated harvest and increasing crop quality and yield. Thus, the development of robotic technologies and their application in agriculture is becoming a growing topic of interest and consideration [6], with an increasing amount of research work being noticed in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…wheat and rice [18]. A brief review concerning various apple harvesting platforms is presented in [5] that additionally develops a software tool for their economic evaluation, while several literature studies on agricultural robotic systems are investigated including the AgROS emulation tool [19], classifying them with regard to their analysis approach and farming operations.…”
Section: Introductionmentioning
confidence: 99%
“…Existing R&M cost estimation techniques are categorized into two groups: mathematical and ANN models. The first group consists of: (a) the American Society of Agricultural Engineers (ASAE) standards [2,4,5,[8][9][10][11][12][13][14] , and (b) curve fitting methods [15][16][17][18][19][20][21] . The mathematical models require a substantial amount of data for accurate estimation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessity of multiple pickings and the mass removal process which leaves either too many overripe or under-ripe fruit, or both, prevented the commercial adoption of such systems for fresh market harvest. Next, orchard platforms/ harvest aids were developed by researchers [13] [14] and commercial companies [15] [16] [17] that reduce worker movement between ladders and bins by positioning the worker and bin on a raised platform. Research done on worker productivity using platforms in narrow-inclined trellises showed a 44% increase over conventional hand harvesting [18], whereas research done in open vase training systems resulted in no improvement [19].…”
Section: Introductionmentioning
confidence: 99%